Legal consequences, measures of prevention and reduction of medical malpractice cases (errors) - A. O. Yanchuk; A. O. Zaporozhchenko; I. P. Katerynchuk; S. O. Kuznichenko; A. V. Kryzhanovska (Zaporozhye State Medical University, 2019)
This work is purposed for determining grounds for legal consequences to come when any medical malpractice cases occur. Aim. The goal of our research is to determine the quintessence features of "medical malpractice (error)" in the medical-legal context so to determine legal consequences of medical malpractices (errors), and to classify the regulatory measures of prevention of medical malpractice cases and reduction of these problems. Methods: semiotical, synergetic, anthropological and hermeneutical, method of normative comparison. Results. Detecting the current medical malpractice (medical error) becomes more complicated due to its definition as highly significant differences in interpreting, understanding, qualifying, finding defects, medical errors and provability of these failures result in the complication of producing efficient legal guarantees for protection of the patient`s right. The peculiarity of this medical and legal substrate is that it synthesizes the awareness of rights and medicine both through the lens of their achievements. A clear vision of such a phenomenon as medical malpractice (error) has a priori significance for the legal environment. It is a sparkling example of the epistemological and gnoseological interaction of the medical and legal knowledge as to determine criteria of medical malpractices is to set "boundaries" of the legal regulation. Here we mean the occurrence of legal consequences in committing an error of law. Conclusions. For a more complete understanding of cases of legal consequences the following regulatory measures of prevention of medical malpractice cases are necessary: establishment of an effective system of prudential internal control of defects in the medical care; specialised training for medical personnel on methods of detection of medical malpractices, their prediction and prompt elimination of possible consequences; instrumental, functional and system-structural measures for reducing risks of medical malpractice, namely: actions for reducing medical errors caused by system determinants (failures, disorders, etc.), actions for reducing medical errors made in prescribing and applying medicaments, medical errors happened because of the medical intervention, surgical in particular; improvement of the legal support of guarantees of patients and doctors rights for a safe delivery of medical aid and prevention of medical errors.